Vapor-liquid phase equilibrium data of CO2 in some physical solvents from 285.19 K to 313.26 K - Gui, X.; Wang, Wei; Wang, C.; Zhang, L.; Yun, Z.; Tang, Z. (American Chemical Society, 2014)
The solubility of CO 2 in polyethylene glycol dimethyl ether (NHD), octamethyl cyclotetrasiloxane (D4), and diethyl succinate (DS) was determined at the temperature variations from 285.19 K to 313.26 K up to 6 MPa by the constant-volume method. Then, Henry's law constant (H) based on mole fraction was obtained by linear fitting of the vapor-liquid phase equilibrium data, and some thermodynamic properties of solutions were also calculated from the correlation of H. The values of H in NHD, D4, and DS vary from 2.5 MPa to 8 MPa and increase in the following order: DS < D4 < NHD, which is identical to the order of the solvents ability to dissolve CO 2 . Additionally, Henry's law constant increases with temperature increase to confirm the solubility of CO 2 decrease in the corresponding solvents for the pressure range studied. © 2014 American Chemical Society.